2017
DOI: 10.1016/j.canlet.2017.09.019
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA HOTTIP modulates cancer stem cell properties in human pancreatic cancer by regulating HOXA9

Abstract: Our previous study demonstrated that long non-coding RNA (lncRNA) HOTTIP was maximally expressed in PDAC, and promoted cancer cell progression and epithelial to mesenchymal transition (EMT). Numerous studies indicated that lncRNAs or EMT supported cancer stem cells. However, the role of HOTTIP in pancreatic cancer stem cells (PCSCs) remains unclear. Here, we evaluated the role and mechanism of HOTTIP in PCSCs. First, we analyzed the relationship between HOTTIP expression and overall or disease-free survival in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
113
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(115 citation statements)
references
References 50 publications
2
113
0
Order By: Relevance
“…20,21,24,28 Recently, Liao et al 22 demonstrated that HOTTIP expression is elevated in coronary artery disease and in tumor necrosis factor-α or platelet-derived growth factor-induced proliferating endothelial cells; moreover, ectopic expression of HOTTIP augments endothelial cell proliferation. Studies have revealed that HOTTIP is highly expressed in small-cell lung cancer, colorectal cancer, pancreatic cancer, and esophageal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…20,21,24,28 Recently, Liao et al 22 demonstrated that HOTTIP expression is elevated in coronary artery disease and in tumor necrosis factor-α or platelet-derived growth factor-induced proliferating endothelial cells; moreover, ectopic expression of HOTTIP augments endothelial cell proliferation. Studies have revealed that HOTTIP is highly expressed in small-cell lung cancer, colorectal cancer, pancreatic cancer, and esophageal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the expression levels of HOTTIP are significantly increased in multiple PDAC cell lines and PDAC specimens (35). HOTTIP interacts with the WD repeat containing protein 5 (WDR5)/mixed lineage leukemia (MLL) complex to enhance the methylation of histone 3 on lysine 4 (H3K4) in order to modulate the proliferation and differentiation of PDAC cells (36,37). Up-regulation of HOTTIP promotes the secretion of IL-6 and expression of PD-L1 in neutrophils, thereby inhibiting the activity of T cells and promoting the immune escape of ovarian cancer cells (38).…”
Section: Hottipmentioning
confidence: 99%
“…Increasing evidence indicates that HOTTIP is overexpressed in prostate cancer, lung cancer, and pancreatic cancer . HOTTIP knockdown impedes cell viability, proliferation, invasion, and angiogenesis in human cancer cells, therefore it is been identified as an oncogenic long noncoding RNA (lncRNA).…”
Section: Introductionmentioning
confidence: 99%